The success rate of hatching green turtles with semi-natural incubation systems in the marine rides of Paloh district - Iswanto, Iswanto; Agam, Beryaldi (Journal of Fisheries and Marine Applied Science, 2024)
Paloh Beach, Sambas Regency is the most potential beach as a green turtle nesting (Chelonia mydas) and is the longest turtle nesting site in Indonesia. The sustainability of green turtles is still an issue that must be resolved. Many factors influence such as extreme climate change, predator disturbance, and human actions so that the green turtle population is declining and even threatened with extinction. The purpose of this study was to determine the success rate of hatching green turtles with semi-natural incubation systems in Paloh District. The location and time of the research were carried out at Wahana Bahari Paloh domiciled in Setinggak Hamlet, Sebubus Village, Paloh District, Sambas Regency, West Kalimantan for 4 months from February to June 2023. The method used is the descriptive method. This research activity includes transferring turtle eggs to semi-natural nests (egg relocation), demolition of semi-natural nests, and calculating the hatchability rate of green turtle eggs. The result of this study is that the success rate of hatchability of green turtle eggs on average is 78.70%